Candida concentrations determined following concentrated oral rinse culture reflect clinical oral signs - Tooyama, Hiroaki (BMC Oral Health, 2015)
BACKGROUND: Oral candidiasis is an infection caused by a yeast-like fungus called Candida. Various methods can be used to isolate Candida from the oral cavity. However, it is difficult to correctly and satisfactorily diagnose oral candidiasis because currently no microbiological or laboratory standards based on samples from the oral cavity are available. The aim of this study is to establish a reliable laboratory test for diagnosing oral candidiasis. METHODS: Oral swab, rinse and concentrated rinse samples were obtained from 200 consecutive outpatients (103 male patients and 97 female patients; mean age, 47.2 years; age range, 9–89 years). Candida colonies from cultured samples were enumerated to compare the sensitivities and specificities of the above sampling methods, and the associations between Candida detection or concentration and the clinical oral signs were examined. RESULTS: The mean colony numbers were 263 ± 590 CFU/swab for the swab method, 2894 ± 6705 CFU/100 μL for the rinse method, and 9245 ± 19,030 CFU/100 μL for the concentrated rinse method. The median numbers were 23 CFU/swab for the swab method, 56 CFU/100 μL for the rinse method, and 485 CFU/100 μL for the concentrated rinse method. Candida was detected in the oral cavity of 33.5 % and 52.0 % of the outpatients by the swab method and concentrated rinse, respectively. Candida concentrations determined by the concentrated rinse were closely related to the severity of the clinical oral signs. The positive predictive values of residual root, redness of the oral mucosa, denture, glossalgia, dry mouth, and taste disorder were useful predictors of oral candidiasis. CONCLUSIONS: Concentrated rinse sampling is suitable for evaluating oral candidiasis, and Candida concentrations examined using this method strongly associated with the oral signs associated with Candida infection.